Trees outside forests in Ghana: current state, spatial distribution, and future projection - Kwadwo Kyenkyehene Kusi (Frontiers in Forests and Global Change)
Trees outside forests (TOF) are increasingly recognized for their vital contributions to environmental sustainability and socioeconomic development. TOF are undervalued and seldom included in national inventories and international reporting frameworks, particularly in Africa. There is a need to estimate the state, spatial distribution, and future projection of TOF in Ghana at the national scale using effective tools such as Geographic Information Systems (GIS) and remote sensing techniques. Environmental Systems Research Institute (ESRI) global land cover data at 10 m resolution was used for this study between 2017 and 2023, and Quantum GIS Modules for Land-Use Change Simulation (MOLUSCE) was used to predict future TOF. The results show that the area occupied by TOF declined from 38.2 to 33.8% at an annual rate of −2.02%, whereas the area occupied by trees inside forests increased from 10.4 to 10.7% in Ghana from 2017 to 2023, respectively. The decline is expected to continue in Ghana, with an annual rate of −0.79% by 2030. Ashanti region and Sekyere Afram Plains North had the largest area of TOF, whereas the Greater Accra region, with its four districts, had the least TOF during the study period in Ghana. TOF hold the second largest area in Ghana and should be recognized in climate change mitigation initiatives in Ghana and the nationwide forest monitoring systems.